2004
DOI: 10.1203/01.pdr.0000136277.10365.84
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Responses to Protein Restriction During Pregnancy in Rat and Translation Initiation Factors in the Mother and Fetus

Abstract: A low-protein diet during pregnancy in the rat results in intrauterine growth restricted (IUGR) fetuses. The adaptive responses of the mother to low-protein diet and the mechanisms of IUGR in this model are not understood. In the present study, we report the maternal metabolic responses to protein restriction and their impact on growth, carcass composition, and translation initiation in the fetus. Pregnant Sprague-Dawley rats were pairfed either a 6% protein (LP, n ϭ 7) or a 24% protein (NP, n ϭ 7) diet from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
4
9
0
Order By: Relevance
“…Maternal protein restriction (60 g protein/kg diet) throughout pregnancy in rats decreased maternal serum concentration of the branched chain amino acids (valine, isoleucine and leucine) by 29-36%, and the threonine concentration was reduced by 80% compared with the control group fed on 180 g protein/kg diet (Rees et al 1999). Similar results have been reported in rats showing significantly decreased maternal serum concentrations of the branched-chain amino acids and/or the total essential amino acids under maternal protein restriction (Bhasin et al 2009;Parimi et al 2004;Rees et al 2006). BeWo cells have been used to study the effects of amino acid restriction on amino acid transport (Jones et al 2006), in which DMEM Glutamax 1 was used as control, while the amino acid deprivation medium was a balanced salt solution containing no nonessential, and 50% essential amino acids used in MEM.…”
Section: Discussionsupporting
confidence: 79%
“…Maternal protein restriction (60 g protein/kg diet) throughout pregnancy in rats decreased maternal serum concentration of the branched chain amino acids (valine, isoleucine and leucine) by 29-36%, and the threonine concentration was reduced by 80% compared with the control group fed on 180 g protein/kg diet (Rees et al 1999). Similar results have been reported in rats showing significantly decreased maternal serum concentrations of the branched-chain amino acids and/or the total essential amino acids under maternal protein restriction (Bhasin et al 2009;Parimi et al 2004;Rees et al 2006). BeWo cells have been used to study the effects of amino acid restriction on amino acid transport (Jones et al 2006), in which DMEM Glutamax 1 was used as control, while the amino acid deprivation medium was a balanced salt solution containing no nonessential, and 50% essential amino acids used in MEM.…”
Section: Discussionsupporting
confidence: 79%
“…The concentration of methionine in the plasma was measured by HPLC (15). An aliquot of plasma was treated with perchloric acid to remove [ 14 C]O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples (0.5 ml) were obtained in heparinized syringes at 240, 270, 300, and 330 min. Respiratory calorimetry measurements were done using an open canopy system as described previously (15).…”
Section: Isotopic Tracer Studiesmentioning
confidence: 99%
“…In a previous study in rat, we had examined the effect of isocaloric protein restriction on the metabolism of the mother and translation initiation factors as indices of protein synthesis in the maternal and fetal liver (Parimi et al, 2004). These data showed that protein restriction in pregnancy resulted in a higher rate of oxygen consumption and lower levels of branched chain amino acids, lysine and histidine early in gestation suggestive of a lower rate of whole body protein turnover as was seen in the non- pregnant animals (Kalhan et al, 2011).…”
Section: One Carbon Metabolism and The Health Of The Mother Fetusmentioning
confidence: 99%